FINANCIAL EDUCATION AND FINANCIAL LITERACY ON MICRO ENTREPRENEUR GROWTH IN INDONESIA - Roslita, Evy (Lembaga Riset dan Pengabdian Masyarakat (LRPM) Institut Bisnis Nusantara, 2023)
Micro, Small, and Medium Entreprises (MSMEs) in Indonesia play an important role in Indonesia's economic growth. The contribution of MSMEs to GDP also reaches 60.5%, and to employment is 96.9% of the total national employment absorption. Therefore, special attention to promoting their financial literacy is needed. It is believed that financial knowledge can make the quality of financial business decisions